2010
DOI: 10.1007/s10517-010-0879-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Suppression of E6 and E7 Virus Oncogenes and Expression of Apoptosis and Cell Cycle Genes in Cervical Cancer Culture

Abstract: The effects of short interfering RNA suppressing the expression of E6 and E7 human papilloma virus (type 18) on the expression of apoptosis and cell cycle genes were studied in HeLa cells. Changes in the transcription profiles were evaluated using DNA microarray and real-time reverse-transcription PCR. Cell transfection with anti-E6 and anti-E7 short interfering RNA moderately reduced the expression of mRNA for CDC25C, GRB2, GTSE1, and PLK1 genes and induced expression of CDKN1A (p21(CIP)) gene mRNA. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Similarly, GTSE1 (G2 and S phase-expressed-1 gene) which is a key regulator of tumor cell migration and metastasis (Penna et al, 2017), was down-regulated in this study. The targeting of this gene in the cervical cancer cell line inhibits culture proliferation as seen by the previous study (Khokhlova et al, 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, GTSE1 (G2 and S phase-expressed-1 gene) which is a key regulator of tumor cell migration and metastasis (Penna et al, 2017), was down-regulated in this study. The targeting of this gene in the cervical cancer cell line inhibits culture proliferation as seen by the previous study (Khokhlova et al, 2010).…”
Section: Discussionsupporting
confidence: 57%
“…In this study, 9-oxo-ODAs downregulated the expression of E6 and E7 in cervical cancer cells, slowed the cell cycle, and induced apoptosis. Previous reports have demonstrated that suppression of HPV oncoprotein expression causes cell cycle inhibition 31 , 32 . Our results indicated that the antitumor effects of 9-oxo-ODAs may involve the E6 and E7 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 9-oxo-ODAs downregulated the expression of E6 and E7 in cervical cancer cells, slowed the cell cycle, and induced apoptosis. Previous reports have demonstrated that suppression of HPV protein expression causes cell cycle inhibition 24,25 . However, the mechanisms by which 9-oxo-ODAs downregulate E6 and E7 expression remain unknown.…”
Section: Discussionmentioning
confidence: 99%